Pathologizing the Crisis: Psychiatry, Policing, and Racial Liberalism in the Long Community Mental Health Movement. (21st December 2018) - Ramos, Nic John
Abstract: The community mental health movement has been generally regarded as a benevolent movement that replaced old notions of psychiatric racism with new ideas about the normality of race. Few studies, however, have explored the movement for its active support for new surveillance and policing strategies, particularly broken windows theory, a policing approach partly responsible for the expansion of prisons in the United States after the 1970s. Looking to racially liberal approaches to psychiatry in the 1960s and 1970s crafted by integrationist psychiatrist Louis Jolyon West and black nationalist psychiatrist J. Alfred Cannon at the University of California, Los Angeles, this essay demonstrates that cultural and biological explanations for racial violence in civil rights and black nationalist discourses renewed surveillance on poor people of color that resulted in increased forms of incarceration, segregation, and discrimination for them by the 1980s. Rather than forward racial justice, I argue that psychiatric discourses arguing for the racial sameness of white and black minds in the 1960s and 1970s relied on scientific and cultural narratives centered on child development, gender, and sexuality that obscured the processes of racial capitalism that continued to produce poverty and sickness in black communities.